Preparation and characterization of natural rubber-polyethylene and natural rubber/polyethylene- clay nanocomposites - Mohd Aidil Adhha Abdullah (Fakulti Sains dan Teknologi, 2011)
The present research aims at studying the influence of organoclay on the properties of natural rubber (NR), low density polyethylene (LDPE) and NR/LDPE blend. Two types of clays, namely montmorillonite,(MMT) (cationic clay) and layered double hydroxide (LDH) (anionic clay) were used in this study.